The Use of Daily Essays to Improve Arabic Writing Skills (an Experimental Study for new students of English Departmen): An Experimental Study for new students of English Language Education Study Programme - Muhammad Abdur Rozaq; Muh. Sabilar Rosyad; Salih Abdulrahman Alsounusi Yousuf Al-Senhaji (Naatiq: Journal of Arabic Education, 2024)
Writing ability is one of the Arabic language skills that is often considered difficult by students in Indonesia. This difficulty is often caused by learning methods that focus more on grammar theory rather than active writing practice. This study aims to evaluate the effectiveness of applying daily essay as a learning approach in improving Arabic writing skills. The method used was an experiment with a pre-test and post-test design on two groups: the experimental group using the daily journal technique and the control group using conventional learning methods. The results showed that the application of daily essays can significantly improve students' writing skills, especially in terms of mastery of vocabulary, grammar, sentence structure, and creative delivery of ideas. The average post-test score in the experimental group reached 85.4, while the control group only reached 76.8. In addition, this technique also had a positive impact on students‘ motivation and participation in the learning process. This study also found some obstacles in applying the daily journal technique, such as students’ difficulties in determining writing topics and teachers' limited time to provide feedback. These obstacles can be overcome by providing more specific topic directions and focusing feedback on certain aspects of students' writing. The results of this study support previous findings which state that consistent writing practice can improve language skills. The daily journal technique proved to be an effective and relevant method to be applied in Arabic language learning, especially in Indonesia. Further research is recommended to examine the application of this technique in other aspects of language skills, such as speaking and reading.